2013
DOI: 10.1103/physreva.88.062111
|View full text |Cite
|
Sign up to set email alerts
|

Twofold transition inPT-symmetric coupled oscillators

Abstract: The inspiration for this theoretical paper comes from recent experiments on a PT -symmetric system of two coupled optical whispering galleries (optical resonators). The optical system can be modeled as a pair of coupled linear oscillators, one with gain and the other with loss. If the coupled oscillators have a balanced loss and gain, the system is described by a Hamiltonian and the energy is conserved. This theoretical model exhibits two PT transitions depending on the size of the coupling parameter . For sma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
213
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(224 citation statements)
references
References 25 publications
10
213
0
1
Order By: Relevance
“…Therefore we call this a Time-Symmetry Breaking Phase Transition (TSBPT) where the imaginary part of the eigenvalue can be regarded as an order parameter that has a singularity at the critical point in terms of a system control parameter [19][20][21][22][23][24][25][26]. Very * stanaka@p.s.osakafu-u.ac.jp recently TSBPT has been experimentally observed in mesoscopic quantum systems [17,27], and also in many analogous optical systems where interesting collective dynamical properties have been studied, such as superradiance and lasing [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore we call this a Time-Symmetry Breaking Phase Transition (TSBPT) where the imaginary part of the eigenvalue can be regarded as an order parameter that has a singularity at the critical point in terms of a system control parameter [19][20][21][22][23][24][25][26]. Very * stanaka@p.s.osakafu-u.ac.jp recently TSBPT has been experimentally observed in mesoscopic quantum systems [17,27], and also in many analogous optical systems where interesting collective dynamical properties have been studied, such as superradiance and lasing [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Spontaneously breaking the PT -symmetry one observes a transition from a real to a complex eigenvalue spectrum [1,3]. Recently it has been impressively demonstrated that PT -symmetry can be realized in wave optical devices [3][4][5][6][7][8][9]. The first studies in this direction were motivated by the fact that the time-dependent Schrödinger equation maps on the paraxial approximation of the electromagnetic wave equation, describing the transverse variation of the electric field [3,10], where the variation on the z axis plays the role of time in the corresponding Schrödinger equation.…”
Section: Introductionmentioning
confidence: 99%
“…PT HPT = H since it is invariant under the combined effect of parity P : {x, y, p x , p y } → {−y, −x, −p y , −p x } and time reversal T : {x, y, p x , p y } → {x, y, −p x , −p y } [1]. Note that we can also choose P : {x, y, p x , p y } → {y, x, p y , p x } for exactly the same purpose.…”
Section: Quantum-mechanical Modelmentioning
confidence: 99%
“…In a recent paper Bender et al [1] discussed the classical and quantum-mechanical versions of a system of two coupled linear oscillators one with gain and the other with loss. When the gain and loss parameters are equal the Hamiltonian derived from the classical equations of motion is PT -symmetric and exhibits two PT -transitions in terms of the coupling parameter.…”
Section: Introductionmentioning
confidence: 99%